The low affinity A2B adenosine receptor enhances migratory and invasive capacity in vitro and angiogenesis in vivo of glioblastoma stem-like cells - Erices, José I.; Niechi, Ignacio; Uribe-Ojeda, Atenea; Toro, María de los Ángeles; García-Romero, Noemí; Carrión-Navarro, Josefa; Monago-Sánchez, Álvaro; Ayuso-Sacido, Ángel; Martin, Rody San; Quezada-Monrás, Claudia (Frontiers in Oncology, 2022)
Glioblastoma (GBM) is the most common and deadly malignant brain tumour, with a patient’s median survival rate from 15 to 17 months. GBM contains a cellular subpopulation known as glioblastoma stem-like cells (GSCs) that persist in hypoxic niches and are capable of infiltrating into healthy brain tissue. For this reason, GSCs are considered as one of the main responsible for GBM recurrence. Hypoxic microenvironment increases extracellular adenosine levels, activating the low affinity A2B adenosine receptor (A2BAR). Adenosine, through A2BAR, is capable of modulating invasiveness, however, its role in the invasion/migration of hypoxic-GSCs is still unknown. The aim of this study is to understand the importance of A2BAR in modulating the migratory/invasive capacity of GSCs under hypoxia. Data analysis from The Cancer Genome Atlas (TCGA) program correlates A2BAR expression with high grade glioma and hypoxic necrotic areas. U87MG and primary culture derived GSCs under hypoxic conditions (0.5% O2) increased A2BAR mRNA and protein levels. As expected, migratory and invasive capacity of GSCs increased under hypoxia, which was counteracted by blocking A2BAR, through the downregulation of MMP9 activity and Epithelial-Mesenchymal Transition marker expression. Finally, in a xenograft mice model, we demonstrate the treatment with MRS1754 did not affect the volume tumour but was able to decrease blood vessel formation and VEGF expression. Our results suggest that extracellular adenosine, through the activation of A2BAR, enhances the migratory and invasive capacity in vitro of GSCs under hypoxic conditions. Targeting A2BAR can be an effective therapy for GBM recurrence.